MULTIDISCIPLINARY APPROACH TO STUDY MIGMATITES: ORIGIN AND TECTONIC HISTORY OF THE NASON RIDGE MIGMATITIC GNEISS, WENATCHEE BLOCK, CASCADES CRYSTALLINE CORE, WA, USA - Stowell Harold H.; Zuluaga C. Carlos A. (Earth Sciences Research Journal)
The Nason Ridge Migmatitic Gneiss of the Cascades Core is a migmatitic unit comprising concordant pelitic schist and gneiss, amphibolite, and tonalite gneiss, and cross cutting tonalite, quartz-rich granitoid, and pegmatite. There are several generations of 'igneous' lithologies (leucosomes = tonalite, quartz-rich granitoid, and pegmatite) some of which are concordant; others clearly crosscut the strongly deformed host rocks. The host rocks are interpreted to be Chiwaukum Schist with metasedimentary (pelitic schist and some gneiss) and metavolcanic(amphibolites) origins. Metamorphic fabric in the Nason Ridge Migmatitic Gneiss is characterized by preferred orientation of platy minerals (continuous schistosity), compositional layering, mineral lineations (elongate grains and grain aggregates), and non-coaxial deformational features (asymmetric augen, grain offsets,rotated porphyroblasts, etc.). Compositional layering is characterized by quartz-plagioclase lenses and patches (mm to cm scale) and by large variations in biotite content. This composite fabric is faulted and folded by mesoscopic structures. The most strongly foliated leucosomes (gneissic tonalites) are generally concordant with the regional trend of foliation, while weakly foliated leucosomes (tonalites) and pegmatite veins crosscut host rock and tonalite gneisses. Thin melanosome layers (biotiteand amphibole schist) are developed locally around quartz - plagioclase lenses and patches. Metamorphism in the Nason Ridge Migmatitic Gneiss and the nearby Chiwaukum Schist likely peaked after intrusion of the Mt. Stuart Batholith ca. 91-94 Ma. Peak temperatures and pressures for the Nason Ridge Migmatitic Gneiss in the Wenatchee Ridge and Pacific Crest areas were 650 - 720 °C and 6 - 9 kbar with a pressure increase of £ 2.0 kbar during metamorphism. Thermodynamic modeling indicates that hydrous partial melting would begin at ca. 660 °C and is relatively pressure independent. Field and petrographic observations, mineral chemistry and thermobarometry, and bulk rock chemistry and thermodynamic modeling of phase equilibria (pseudosections) applied to the Nason Ridge 235Migmatitic Gneiss indicate that at least some of the leucosome bodies were derived by local partial melting. The clearly intrusive character and the sharp contacts between some tonalite leucosome bodies and host rock support an externally derived origin for these tonalite melts. However, some of these bodies may have originated from partial melting of the host Chiwaukum Schist and traveled a short distance before crystallization, or have been modified by deformation so as to obscure textural evidence for local derivation. Results are compatible with derivation of leucosome rocks in the Nason Ridge Migmatitic Gneiss from two non-exclusive processes: partial melting of the host rock and intrusion of externally derived tonalite melts.